The association between parental views on dietary quality and physical activity levels. (March 2020) - S Earnesty, Dawn; Mphwanthe, Getrude; M Shipp, Gayle; Kelleher, Deanne; Plasencia, Julie; Quilliam, Elizabeth Taylor; Rifon, Nora J; J Weatherspoon, Lorraine
Introduction: Numerous external factors, including parental influences, impact the dietary quality and physical activity of children. In this study, we examined if parental views were associated with the dietary quality and physical activity of children. Design: A cross-sectional observational study was used to recruit and collect data from a purposive sample of 176 parents and their children, 4–11 years of age. Setting: A suburban school district in Michigan, USA. Methods: Healthy Eating Index (HEI) 2005 scores were calculated from child food frequency data, and bivariate linear regression was used to test associations between the total HEI 2005 and fruit, total vegetable, solid fats and added sugars (SoFAAs) and saturated fat dietary components, as well as relative to the parent's views of raising children. Multivariate linear regression models were used to evaluate the relationship between the HEI score and the parental views. Multinomial linear regression was used to test associations between physical activity and parental views on their children's behaviours related to health outcomes. Results: Children whose parents had firm parenting views were significantly more likely to eat vegetables and foods and beverages that were lower in saturated fat and added sugars. Parental views on child behaviour were not associated with physical activity of children. Conclusion: Parental views on child behaviour and other influences on child dietary quality are complex. As a result, health care professionals including dieticians should use a multifaceted approach to assess how parental views shape guidance regarding children's dietary quality and subsequent health.